Opinions on memorandum on 'help for Spain' submitted to the Spain Campaign Committee
1938 036-0009-005 -2- I consider this document as being of major importance and it would give me great pleasure if the British friends of our cause were to accord to it the attention it deserves, which I trust will be the case. I take this opportunity to thank you very heartily for the disinterested help you are giving to my country. Sincerely yours, (Signed) JOSE da CASA. Agricultural Attache. (3) The COMMERCIAL ATTACHE TO THE SPANISH EMBASSY - Dear Sir, You already know, I believe, that we think highly of the work of Voluntary Industrial Aid for Spain, and are grateful to those who have helped in its work. The latest product of the organisation - the Memorandum to the Spain Campaign Committee of the Parliamentary Labour Party - to my mind, is one of the most effective contributions towards real aid to Spain. It displays the attitude called for by the present situation, and it sees the problem as a whole, yet deals in a very practical way with details. It is scientific and also has imagination. This Memorandum should serve as a basis for the combination of the English people's efforts to help the Spanish Democracy. I think the Spanish Commercial Authorities should be made aware of your work, and I shall send to them copies of the translation which I understand you are having prepared. Friends of Republican Spain will, I am sure, join with me in hoping that your organisation will receive the support which is justly due to it. Yours faithfully, (Signed) D.F. SHAW. Commercial Attache to the Spanish Embassy. 292/946/36/11(ii)